Plasma proteomic profiling reveals molecular signatures of thermal stress and bleaching in the photosymbiotic giant clam Tridacna crocea - Mao, Fan; Jin, Xiaoyang; Chen, Chenghao; Yi, Wenjie; Zhang, Yang (Frontiers in Ecology and Evolution, 2025)
IntroductionCoral reef ecosystems are increasingly threatened by climate change-induced thermal stress, leading to widespread bleaching events. Giant clams (Tridacna spp.) are key photosymbiotic reef inhabitants that harbor extracellular dinoflagellate symbionts (Symbiodiniaceae) and contribute to reef structure and nutrient cycling. However, the molecular mechanisms underlying their response to heat stress remain poorly understood.MethodsA non-lethal plasma sampling technique was employeed to characterize the proteomic profile of Tridacna crocea under controlled thermal stress. iTRAQ-based quantitative proteomics profiled host plasma proteins, and integrated transcriptomic analyses across five tissues assessed tissue-specific expression and the contribution of secretory factors to host–symbiont interactions.ResultsWe quantified 554 host plasma proteins that differentially expressed, with significant enrichment in immune response pathways, lectin-mediated recognition, and complement system components. Integrated transcriptomic analysis of five tissues revealed tissue-specific expression patterns and underscored the role of secretory proteins in host-symbiont interactions. Key biomarkers, including C1q domain-containing proteins and lectin family members, exhibited consistent dysregulation under stress, reflecting a shift from symbiosis maintenance to immune defense.DiscussionThese data delineate a plasma proteomic signature of bleaching in T. crocea and implicate innate immune pathways in restructuring host–symbiont dynamics under heat stress. The non-lethal plasma assay, coupled with proteogenomic readouts, offers a scalable framework for monitoring giant clam health and, by extension, reef condition under ongoing climate change.